Noiseless steganography the key to covert communications - Desoky, Abdelrahman (CRC Press, 2012)
IntroductionSteganography: Definition, Current State, and ConcernsNoiseless Steganography (Nostega) Paradigm Summary of the ContributionsBook OutlineConclusionRelated WorkText SteganographyNon-Textual SteganographyGraphstega: Graph Steganography MethodologyGraphstega MethodologyOther Steganographic Cover TypesCommunications ProtocolConclusionChestega: Chess Steganography MethodologyChestega MethodologyChestega ImplementationConclusionEdustega: Education-Centric Steganography MethodologyEdustega MethodologyEdustega ImplementationConclusionSumstega: Summarization-Based Steganography MethodologyAutomatic Summarization OverviewSumstega CarriersSumstega MethodologyConclusionMatlist: Mature Linguistic Steganography MethodologyIntroductionMatlist MethodologyMatlist ImplementationConclusionNORMALS: Normal Linguistic Steganography MethodologyNORMALS MethodologyNORMALS ImplementationPerformanceConclusionHeadstega: Steganography MethodologyHeadstega MethodologyHeadstega ImplementationConclusionJokestega: Automatic Joke Generation Based Steganography MethodologyAutomatic Joke Generation Jokestega MethodologyJokestega ImplementationConclusionListega: Steganography MethodologyListega MethodologyListega ImplementationConclusionNotestega: Steganography MethodologyAutomatic Note TakingNotestega MethodologyNotestega ImplementationConclusionSteganalysis ValidationTraffic AttackContrast and Comparison AttacksLinguistics AttacksStatistical SignatureConclusionConclusion and Future WorkContributionsBitrateFinal Conclusion and Future WorkBibliographyIndex.
Includes bibliographical references
Keywords: Data encryption (Computer science); Confidential communications; Electronics in espionage; Data transmission systems; Coding theory; Chiffrement (Informatique); Secret professionnel; Électronique dans l'espionnage